Multifunctional Effect of p‐Doping, Antireflection, and Encapsulation by Polymeric Acid for High Efficiency and Stable Carbon Nanotube‐Based Silicon Solar Cells. Issue 1 (20th November 2019) - Qian, Yang; Jeon, Il; Ho, Ya‐Lun; Lee, Changhyun; Jeong, Sujeong; Delacou, Clement; Seo, Seungju; Anisimov, Anton; Kaupinnen, Esko I.; Matsuo, Yutaka; Kang, Yoonmook; Lee, Hae‐Seok; et al.
Abstract: Silicon solar cells among different types of solar energy harvesters have entered the commercial market owing to their high power conversion efficiency and stability. By replacing the electrode and the p ‐type layer by a single layer of carbon nanotubes, the device can be further simplified. This greatly augments the attractiveness of silicon solar cells in the light of raw material shortages and the solar payback period, as well as lowering the fabrication costs. However, carbon nanotube‐based silicon solar cells still lack device efficiency and stability. These can be improved by chemical doping, antireflection coating, and encapsulation. In this work, the multifunctional effects of p ‐doping, antireflection, and encapsulation are observed simultaneously, by applying a polymeric acid. This method increases the power conversion efficiency of single‐walled carbon nanotube‐based silicon solar cells from 9.5% to 14.4% and leads to unprecedented device stability of more than 120 d under severe conditions. In addition, the polymeric acid‐applied carbon nanotube‐based silicon solar cells show excellent chemical and mechanical robustness. The obtained stable efficiency stands the highest among the reported carbon nanotube‐based silicon solar cells. Abstract : Polymeric acid dopants in single‐walled carbon nanotube‐laminated silicon solar cells show multifunctional effects; strong and permanent p‐ doping, antireflection, and encapsulation. A record‐high power conversion efficiency of 14.4% with a device stability of more than 120 d is obtained herein owing to the multifunctional effects that improve all three photovoltaic parameters upon application of the dopant.